Using the Rasch Model to Measure Students' Argumentative Ability in the Context of Socioscientific Issues About the Covid-19 Pandemic - Amarto, Usman; Yusup, Muhamad; Kistiono, Kistiono (UIN Fatmawati Sukarno Bengkulu, 2022)
Argumentation plays an essential role in developing a critical thinking and understanding or interpreting a central idea of the existing problem, In addition, students need arguments to strengthen understanding and knowledge in the learning process. Socioscientific Issues is a combination of social issues involving moral and ethical components and their relevance to science. This study aims to determine the argumentation ability of junior high school students in the context of socioscientific issues with the topic of the Covid-19 Pandemic. The research method used is descriptive research with careful decision-making and description of an educational phenomenon. The subjects of this study were 133 students, consisting of grades 9 in several junior high schools in Abab District, Penukal Abab Lematang Ilir Regency. The technique of collecting research data employs a test with a total of three essay questions. Data from the study were analyzed using the Rasch model. The result showed that the argumentation skills of junior high school students were 57,29 out of 100 logits. This result indicates that, on average, students can put forward arguments by providing reasons that support their arguments.